Composting of Organic Residues as Influenced by Effective Microorganisms and Earthworms - NAIK, S.; DODAKE, S. B. (Journal of the Indian Society of Coastal Agricultural Research, 2016)
A study was undertaken at central experimental station, Wakawali, Maharashtra to evaluate the influence of effective microorganisms and earthworms on compositing of organic residues. There was a decrease in C:N ratio of all the residues during composting. The C:N ratio was brought down below 15 in all the treatments on 150th day of composting. The maximum reduction in C:N ratio was observed in Shivan leaves (68.95%) followed by Ain leaves (66.56%). Inoculation of Eudrilus eugineae resulted significantly decrease in C:N ratio than Eisenia foetida. Composting of organic residues with earthworms and EM solution resulted in significant increase in cation exchange capacity 86.83 c mol (p+) kg-1. Inoculation of E. eugineae was found to be superior as compared to E. foetida in increasing CEC 84.83 C mol (p+) kg ha-1. There was increase in humic acid and fulvic acid content of all the four crop residues under study. Humification of residues was better with E. eugineae than E. foetida. Inoculation of E. foetida significantly increased the fulvic content.